Evapotranspiration, carbon dynamics and water use efficiency in a drip-irrigated olive orchard in arid coastal western South America - (:unkn) unknown (Elsevier BV, 2024)
The primary climatic characteristic of olive cultivation in Peru is the coastal desert environment with moderate temperatures, minimal precipitation, and high atmospheric water content during the winter season. This report presents a comprehensive study ...
Keywords: Evapotranspiración; Eficiencia hídrica